An analysis of parental satisfaction with school - Jerrim, John; Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (My University, 2022)
This article presents an analysis of factors which are important in the satisfaction with schools during primary education by families. The empirical evidence herein is based on students attending primary education in Spain, a country with a highly centralized school system. The follow-up of students during this period allows to analyse the progression of parental satisfaction. A number of parent and school-related factors have been found to be statistically reliable predictors of parental satisfaction. We highlight that not only educational progress, but also child well-being and self-confidence are significant. This evidence suggests that the design of educational programs which promotes the development of soft-skills can increase parental satisfaction with the school.
Keywords: Familia; Enseñanza primaria; Satisfaction; Parents; Self-confidence